Carbonic anhydrase IX as a novel candidate in liquid biopsy - Ozen Ozensoy Guler; Claudiu. T. Supuran; Clemente Capasso (Taylor & Francis Group, 2020)
Among the diagnostic techniques for the identification of tumour biomarkers, the liquid biopsy is considered one that offers future research on precision diagnosis and treatment of tumours in a non-invasive manner. The approach consists of isolating tumor-derived components, such as circulating tumour cells (CTC), tumour cell-free DNA (ctDNA), and extracellular vesicles (EVs), from the patient peripheral blood fluids. These elements constitute a source of genomic and proteomic information for cancer treatment. Within the tumour-derived components of the body fluids, the enzyme indicated with the acronym CA IX and belonging to the superfamily of carbonic anhydrases (CA, EC 4.2.1.1) is a promising aspirant for checking tumours. CA IX is a transmembrane-CA isoform that is strongly overexpressed in many cancers being not much diffused in healthy tissues except the gastrointestinal tract. Here, it is summarised the role of CA IX as tumour-associated protein and its putative relationship in liquid biopsyfor diagnosing and monitoring cancer progression.